2020
DOI: 10.1016/j.ymthe.2019.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Novel mRNA-Based Therapy Reduces Toxic Galactose Metabolites and Overcomes Galactose Sensitivity in a Mouse Model of Classic Galactosemia

Abstract: Classic galactosemia (CG) is a potentially lethal inborn error of galactose metabolism that results from deleterious mutations in the human galactose-1 phosphate uridylyltransferase (GALT) gene. Previously, we constructed a GalT À/À (GalT-deficient) mouse model that exhibits galactose sensitivity in the newborn mutant pups, reduced fertility in adult females, impaired motor functions, and growth restriction in both sexes. In this study, we tested whether restoration of hepatic GALT activity alone could decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 53 publications
0
40
0
2
Order By: Relevance
“…The required repeated dosing of this therapeutic modality tends to raise concerns about immunogenicity and therapy burden for the patients. As with gene therapy targeting, potential long-term adverse effects therapeutic index and dosing interval of mRNA remain important challenges for the future [ 60 , 68 , 70 ]. The transient nature of the mRNA requiring repeated dosing to remain effective also bears an advantage, by allowing individual dose titration and cessation of therapy if necessary [ 60 , 68 , 70 ].…”
Section: Potential Therapiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The required repeated dosing of this therapeutic modality tends to raise concerns about immunogenicity and therapy burden for the patients. As with gene therapy targeting, potential long-term adverse effects therapeutic index and dosing interval of mRNA remain important challenges for the future [ 60 , 68 , 70 ]. The transient nature of the mRNA requiring repeated dosing to remain effective also bears an advantage, by allowing individual dose titration and cessation of therapy if necessary [ 60 , 68 , 70 ].…”
Section: Potential Therapiesmentioning
confidence: 99%
“…Several preclinical studies evaluating the potential of systemically administered mRNA in metabolic disorders have shown that mRNA provides transient, half-life dependent protein expression, while bearing a low risk of insertional mutagenesis and maintaining dose-responsiveness [ 67 , 68 , 69 , 71 , 72 , 73 , 74 , 75 ]. This therapeutic approach is being explored in classic galactosemia using lipid nanoparticles as delivery system.…”
Section: Potential Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipid nanoparticles are composed of phospholipids, sterols and polyethylene glycol ( 80 )-conjugated lipids, which protect the mRNA from nuclease degradation and immune responses and help in their cellular uptake ( 81 ). mRNAs encapsulated in LNPs have been trialled in animal models of methylmalonic acidaemia ( 82 ), acute intermittent porphyria ( 83 ), ornithine transcarbamylase ( 84 ) deficiency ( 85 ), arginase deficiency ( 86 ) and galactosaemia ( 87 ). Phase I/II clinical trials have been initiated in OTC patients to test the safety and efficacy of OTC mRNA formulated in lipid nanoparticles ( 76 ).…”
Section: Introductionmentioning
confidence: 99%